2015
DOI: 10.21103/article5(2)_cr2
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between the Levels of MMP-9, TIMP-1, and Zinc in Biological Samples of Patients with Carotid Atherosclerosis

Abstract: The aim our study was to evaluate the levels of zinc in blood serum, hair, and specimens of carotid artery atherosclerotic plaques (CAAPs) and their relationship to levels of MMP-9 and TIMP-1 in the serum of patients with stable and unstable CAAPs.Material and Methods: The study included 73 patients (55 men and 18 women) aged from 46 to 88 years (mean age 65.96±1.07 years) with CAAPs. The control group consisted of 10 healthy subjects of similar age and gender. The patients were divided into two groups dependi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 21 publications
(26 reference statements)
1
2
0
Order By: Relevance
“…TIMP-1 is a diagnostic marker for diabetes, in this study, the expression level of TIMP-1 was significantly increased in diabetic and cardiovascular diabetic patients than normal volunteers, also increased significantly in cardiovascular, diabetic patients than other diabetic groups, higher levels of circulating TIMP-1 was connected with the higher risk of diabetes and cardiovascular demise. This finding was consistent with Usmanova [ 20 ], furthermore, Lee and his colleagues who found that plasma TIMP-1 concentration was significantly raised in type II diabetic patients [ 21 ]. Also in this study, the TIMP-1 expression level was significantly higher in diabetic patients with cardiovascular diseases (CVD) than in those without cardiovascular diseases, these were in agreement with Papazafiropoulou and Tentolouris results [ 22 ].…”
Section: Discussionsupporting
confidence: 90%
“…TIMP-1 is a diagnostic marker for diabetes, in this study, the expression level of TIMP-1 was significantly increased in diabetic and cardiovascular diabetic patients than normal volunteers, also increased significantly in cardiovascular, diabetic patients than other diabetic groups, higher levels of circulating TIMP-1 was connected with the higher risk of diabetes and cardiovascular demise. This finding was consistent with Usmanova [ 20 ], furthermore, Lee and his colleagues who found that plasma TIMP-1 concentration was significantly raised in type II diabetic patients [ 21 ]. Also in this study, the TIMP-1 expression level was significantly higher in diabetic patients with cardiovascular diseases (CVD) than in those without cardiovascular diseases, these were in agreement with Papazafiropoulou and Tentolouris results [ 22 ].…”
Section: Discussionsupporting
confidence: 90%
“…Thus, they play an important role in immunity and angiogenesis, whereby their dysregulation may contribute to inflammation or atherosclerosis [ 42 , 43 ]. Jagadeesha et al [ 44 ] have reported that the activation of zinc-dependent endopeptidase MMP9 enables cell migration, while other authors have shown significant increasing of the MMP9 serum levels and lower zinc concentration in patients with unstable atherosclerotic plaque [ 45 ]. According to research, high MMP9 serum concentrations may increase the risk of atherosclerosis.…”
Section: Introductionmentioning
confidence: 99%
“…Zinc regulates the proinflammatory cytokine expression [27], in which white adipose tissue produces interleukin-6 stimulating the secretion of CRP (C-reactive protein) in liver [28]. Zinc influences the expression of PPARs-α (peroxisome proliferator-activated receptors α), which plays a key role in the glucose and lipoprotein metabolism [29,30]. Zinc supplementation has been reported to decrease the total cholesterol, LDL cholesterol, and triglycerides and increase the HDL cholesterol [26,31].…”
Section: Discussionmentioning
confidence: 99%